2023
DOI: 10.1159/000529266
|View full text |Cite
|
Sign up to set email alerts
|

Medical or Common Knowledge? Knowledge of Medical Professionals on Obesity Diagnosis Criteria and Treatment

Abstract: Introduction: Proper diagnosis of obesity and effective treatment requires an interdisciplinary healthcare approach. Nevertheless, obesity remains under-identified and under-treated. Academic knowledge concerning obesity pathology, diagnosis, and treatment is advancing, it is not clear whether this translates into clinical practice. The goal of the study was to assess the knowledge of Healthcare Professionals (HCPs) on obesity, and particularly on the criteria for diagnosis as well as for conservative and surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…To the best of our knowledge, this study is one of the two studies conducted in Poland that compare knowledge on obesity among different healthcare professionals. The earlier study, published in 2023 [37], had a smaller group of 184 respondents and substantially differed in the composition of the study group, including 52.2% of physicians, 20.7% of nurses, and 19.0% of physiotherapists compared to 58.7% of physicians, 17.0% of dietitians, and 24.3% of other healthcare professionals (including nurses, physiotherapists, pharmacists, dentists, and paramedics). Interestingly, no statistically significant differences in knowledge were observed among representatives of different medical professions in that study, in contrast to our research, where several such correlations were found.…”
Section: Discussionmentioning
confidence: 97%
“…To the best of our knowledge, this study is one of the two studies conducted in Poland that compare knowledge on obesity among different healthcare professionals. The earlier study, published in 2023 [37], had a smaller group of 184 respondents and substantially differed in the composition of the study group, including 52.2% of physicians, 20.7% of nurses, and 19.0% of physiotherapists compared to 58.7% of physicians, 17.0% of dietitians, and 24.3% of other healthcare professionals (including nurses, physiotherapists, pharmacists, dentists, and paramedics). Interestingly, no statistically significant differences in knowledge were observed among representatives of different medical professions in that study, in contrast to our research, where several such correlations were found.…”
Section: Discussionmentioning
confidence: 97%
“…Two Polish publications from 2021 and 2023 also addressed attitudes towards the discrimination of patients with obesity ( 23 ) and the level of knowledge about obesity among medical professionals ( 24 ). They were based on a custom questionnaire and in-volved 184 medical professionals.…”
Section: Discussionmentioning
confidence: 99%
“…The second study assessed the knowledge about obesity. Percentage of 67.1 of respondents provided correct answers, with better accuracy in regard to obesity diagnosis (70.1%) than treatment methods (64.6%) ( 24 ). However, neither of these studies utilised FPS or any other standardised tool, nor included direct questions evaluating stigmatisation reported by respondents.…”
Section: Discussionmentioning
confidence: 99%